Preggers seatbelt v 2.0 / Wan Mohd Farid Wan Zakaria, Addin Burhanuddin and Muhammad Sharazad Haris - Wan Zakaria, Wan Mohd Farid; Burhanuddin, Addin; Haris, Muhammad Sharazad (Universiti Teknologi MARA, Perak, 2020)
This product design presents a new approach and design in enhancing safety for pregnant mothers when they are driving a car or as a passenger in the car through the innovation of the safety seatbelt for them that is called as PREGGERS seatbelt. The product emphasized on cost saving, easy and time efficient during fixing works or installation. The idea behind this innovative creation is nevertheless innovating from an existing 3-point safety belt that caused discomfort to pregnant mothers (either as a driver or as a passenger) to a modern 5-point safety belt that could provide improved safety measures and at the same time providing better comfort to them. This product also is created to reduce or minimize the rate of traffic fatalities and or injuries (i.e. death, miscarriage and etc.) to the pregnant mothers, let say, if they were involved in a traffic crash. The benefits of this product are to warrants the concept of comfort and portability which mean the product is very easy to setup (no sweat) to any type of available vehicles or any types of car seat in the market and at the same time, design of the seatbelt can make the pregnant women feel comfortable and give protection to the them and the baby in the womb whenever they using it.